Analysis BI Rate and Return of Third Party Fund On Rate of Third PartyFund onIslamic Banking in Indonesia - Ari Kristin Prasetyoningrum (Conference In Business, Accounting, And Management (CBAM), 2015)
The concept of Sharia banks is different with interest-based conventional banks. Profit sharing system in the Sharia banks has unique characteristics because it must always be submissive and obedient to the rules and principles of sharia. This has implications for the entire activities ofSharia banks, Sharia banks will thus experience the risks caused by its activities. Depositors entrust their funds for Sharia banks to be managed by the bank so that it will generate a return for the depositor and the bank. Therefore, Sharia banks should be run in a professional manner so as to maintain the loyalty of its customers and is able to provide a return that is generally competitive. The objective of this research is to examine the influence Return of the Third Party Funds (Return of TPF) and the BI rate on the rate of Third Party Funds (Rate of TPF). This research is an explanatory research using path analysis model and census technique on Sharia Business Board (SBB) in Indonesia. data used in this research is a secondary data derived from historical data of Islamic banking from the data obtained through the official website of Bank Indonesia in the period of 2010 - 2012. The results of this research indicate that: 1) BI rate significantly influences Return of Third Party Funds resulting in p-value <0,01 with the direction of a negative relationship, 2) Return of Third Party Funds significantly effects on the rate of Third Party Funds with the direction of positive relationships, and 3) BI rate significantly negative effect on the rate of Third Party Funds. Keywords: Islamic Bank, BI Rate, Return, TPF (Third Party Funds)